Soil Quality and Pomelo Productivity as Affected by Chicken Manure and Cow Dung - Le Van Dang; Ngo Phuong Ngoc; Ngo Ngoc Hung (The Scientific World Journal)
Fruit orchards in the Vietnamese Mekong Delta (VMD) are severely degraded due to many factors, such as low organic matter content, soil acidification, and poor soil management. Organic manures are considered to be a soil conservation measure that decreases soil degradation and acidity. This study aimed to evaluate the impacts of soil organic amendments on the improvement of soil fertility and pomelo productivity. Two soil amendments, namely, chicken manure (CM) and cow dung (CD), were investigated for a period of three years at three pomelo orchards. The soil quality was assessed in two depths (0–20 and 20–50 cm), including the soil pH, electrical conductivity (EC), total nitrogen (Ntot), available phosphorus (Pavail), soil organic matter (SOM), bulk density (BD), and exchangeable cations (Ca, Mg, and K). The results indicated that CD and CM improved soil fertility in topsoil layer (0–20 cm) due to an increase in soil pH, SOM, exchangeable Ca, Ntot, and Pavail. In addition, soil BD significantly reduced after CD and CM were supplied in the three consecutive years of study. The soil quality properties that significantly affected pomelo yield were SOM, Ntot, Pavail, and soil BD. Thus, these soil qualities may be considered as key factors for determining and assessing soil quality in fruit orchards in the VMD. More studies on the influence of organic manures on nutrient uptake and pomelo fruit quality are warranted.